Decouple dependencies in your infrastructure as code (Manning Publications Co., 2021)
How do you decouple dependencies in your infrastructure as code so that you can update one without affecting the other? In this stream, Rosemary Wang (the author of "Patterns and Practices for Infrastructure as Code") uses Python, HashiCorp Terraform, and Amazon Web Services (AWS) to apply the principle of dependency injection to infrastructure as code.